2001
DOI: 10.1017/cbo9780511607530
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Electoral Politics

Abstract: This book asks what distinguishes peaceful plural democracies from violent ones and what distinguishes violent ethnic groups from peaceful ones within the same democracy. Contrary to conventional wisdom, it suggests that ethnic groups and their political demands are not inherently intransigent and that violence is not a necessary corollary of ethnic politics. The book posits that ethnic identity serves as a stable but flexible information shortcut for political choices, influencing party formation and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 134 publications
2
69
0
4
Order By: Relevance
“…Moreover, our group-level analysis leaves out an important layer of political actors, such as political parties and rebel organizations, which usually are the directly responsible and active agents in the outbreak of conflicts. Information about such organizations can be very helpful in further evaluating competing explanations of the influence of ethnic politics on civil war violence (see Birnir, 2007). The current research design, based on yearly observations, is relatively crude as regards the precise sequence of elections and violence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our group-level analysis leaves out an important layer of political actors, such as political parties and rebel organizations, which usually are the directly responsible and active agents in the outbreak of conflicts. Information about such organizations can be very helpful in further evaluating competing explanations of the influence of ethnic politics on civil war violence (see Birnir, 2007). The current research design, based on yearly observations, is relatively crude as regards the precise sequence of elections and violence.…”
Section: Resultsmentioning
confidence: 99%
“…8. In an earlier version we followed Birnir (2007) and relied on International Institute for Democracy and Electoral Assistance (IDEA's) coding using the Quality of Government data set (Teorell, Charron, Samanni, Holmberg, & Rothstein, 2009). Careful checking, however, revealed that the coverage of the IDEA data seemed incomplete, and they cannot be assumed to cover all elections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their Minorities at Risk (MAR) dataset broke new ground as regards the political relevance of ethnic groups and soon became the standard source for studies of ethnic mobilization, protest, and ethnic group rebellion (see, e.g., Birnir 2007;Gurr and Moore 1997;Ishiyama 2009;Olzak 2006;Walter 2006).…”
Section: Previous Datasets On Ethnicitymentioning
confidence: 99%
“…De igual forma, un predictor del desempeño de los partidos indígenas es la magnitud de distrito. Cuando el número de escaños disponibles en cada unidad geográfico-electoral es más alto, aumentan las probabilidades de éxito para estos partidos y para colectividades más pequeñas (Coppedge, 1997;Birnir, 2006).…”
Section: Enfoques Teóricos Sobre La Conducta Electoralunclassified